A Descriptive Study of Students’ Writing Abilityin Recount Text Of The Eighth Year Students at Mts Rogojampi - Herlina Suci; Wageyono; Arin Inayah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2019)
The purpose of this research is intended to draw the students’ writing ability of recount text used by the English teacher in Eighth year student at MTs Rogojampi in the academic year 2017/2018. The general problem of this study is how is the students’ writing ability of recount text used by the English teacher in Eighth year student at MTs Rogojampi in the academic year 2017/2018. The primary data are taken from questionnaire and the secondary data are taken from interview. The respondents of the research are the Eighth year student at MTs Rogojampi in the academic year 2017/2018. The total numbers of respondents are 60 students in the population that uses purposive sampling. In this research, the researcher uses the questionnaire as data collecting method. There are 70,42% mean score of orientation, 76,7% mean score of series of events, 72,9% mean score of re-orientation aspect, 54,58% mean score of grammar, and 54,58 mean score of vocabulary aspects. The result of questionnaire is the Eighth year students at MTs Rogojampi in the academic year 2017/2018 are good enough in writing recount text. It is fair enough to say that the student needs more improvement from the way how they learn English, how to write a good paragraph and also knowing the category of the text, especially conducting to recount text. This research can be used as consideration in selection of writing ability, especially about recount text.